RETRACTED: Long Noncoding RNA LOC400043 (LINC02381) Inhibits Gastric Cancer Progression Through Regulating Wnt Signaling Pathway - Jafarzadeh, Meisam; Soltani, Bahram M. (Frontiers in Oncology, 2020)
Gastric cancer is one of the common causes of cancer mortality worldwide, with a low survival rate for the affected people. Recent studies have revealed the key role of long non-coding RNAs (lncRNAs) in the development and progression of many cancers, including gastric cancer. Looking for the potential molecular regulators of gastric cancer incidence and progression, LINC02381 was identified as a downregulated lncRNA in gastric cancer tissues by analysis of available microarray and RNA-seq data and RT-qPCR confirmed this differential expression. MiR-21, miR-590, and miR-27a miRNAs were predicted to be sponged by LINC02381, and dual luciferase assay verified LINC02381 as a competitive endogenous RNA (CeRNA), which binds to them. Furthermore, we found that increased expression of LINC02381 attenuates Wnt pathway activity. Also, functional analysis indicates that LINC02381 arrests cell cycle, increases apoptosis and caspase activity, and reduces cell survival and proliferation rate of the human gastric cancer cell lines AGS and MKN45. Moreover, EMT analysis showed that LINC02381 is involved in gastric cancer progression and inhibits metastasis. Overall, this work for the first time introduces LINC02381 as a CeRNA involved in gastric cancer and provides novel insight into the molecular pathogenesis of gastric cancer.